Organizational creativity‐innovation process and breakthrough under time constraints: Mid‐point transformation. (17th July 2019) - April, Sharone; Oliver, Amalya L.; Kalish, Yuval
Abstract : Time, as a constraining resource, is an important factor in organizational creativity processes. Yet we know little about its role in influencing the creative‐innovative process. This paper uses a case study to integrate three process‐oriented theories concerning the importance of process mid‐points and breakthrough as time resources dissipate. The context we examine is the design process of an exhibition of industrial innovations at the Science Museum in Jerusalem. We argue that actors select a course of action at approximately the temporal mid‐point of a process and that this course of action is itself creative and leads to a breakthrough transformation. Two types of mid‐point creative breakthrough transformation are classified as recombining and pruning. We suggest a theoretical integration and further directions for research.